Propofol Treatment Inhibits Constitutive Apoptosis in Human Primary Neutrophils and Granulocyte-Differentiated Human HL60 Cells. - Chung-Hsi Hsing; Chia-Ling Chen; Wei-Chieh Lin; Chiou-Feng Lin (PLoS ONE, 2015)
Apoptosis regulation is essential for neutrophil homeostasis. We previously demonstrated that a process involving glycogen synthase kinase (GSK)-3β determines neutrophil apoptosis. As for this apoptotic process, an overdose of propofol (2,6-Diisopropylphenol; 25 μg/ml or 140 μM) also causes GSK-3β-mediated macrophage apoptosis; however, the early deactivation of GSK-3β with low-dose propofol has been shown. Therefore, we hypothesize that low-dose propofol may induce neutrophil survival via GSK-3β inactivation. Following in vitro culture, the therapeutic concentration of propofol (10 μg/ml or 56 μM) treatment decreased constitutive apoptosis in isolated human primary neutrophils and in granulocyte-differentiated HL60 cells after all-trans retinoic acid (1 μM) treatment. The inactivation of phosphatidylinositol 3-kinase (PI3-kinase)/AKT and the activation of GSK-3β results in myeloid cell leukemia 1 (Mcl-1) down-regulation, the loss of the mitochondrial transmembrane potential, and caspase-3 activation in these cells, which is accompanied by apoptosis. Notably, propofol treatment attenuates these effects in a PI3-kinase-regulated manner. We found that propofol initiates PI3-kinase/AKT-mediated GSK-3β inactivation and Mcl-1 stabilization, rescuing the constitutive apoptosis in primary neutrophils and granulocyte-differentiated acute promyelocytic leukemia HL60 cells.